Physiological Effect of Cutting Height and High Temperature on Regrowth Vigor in Orchardgrass - Jones, Gordon B.; Alpuerto, Jasper B.; Tracy, Benjamin F.; Fukao, Takeshi (Frontiers in Plant Science, 2017)
Producers of orchardgrass (Dactylis glomerata L.) hay in the Mid-Atlantic US have experienced a reduction in regrowth vigor and a decline in the persistence of their swards. The common management practice for the region is to harvest the first growth of hay by cutting at 2.5–7.5 cm height in May or June. We hypothesize that high temperature and low cutting height interact to limit the regrowth rate. To test this, orchardgrass plants were cut to either 2.5 or 7.5 cm and then placed into environmentally controlled chambers with a constant temperature of 20 or 35°C. Stubble was harvested on days 0, 1, 3, and 11 following cutting and subjected to metabolite analysis. Photosynthetic parameters were measured in the regrown leaves on days 3 and 11, and regrowth biomass was recorded on day 11. Under optimal growth temperature (20°C), vegetative regrowth upon defoliation was significantly enhanced when more stubble tissue remained. However, this advantage was not observed under heat stress. Defoliation generally decreases the abundance of carbohydrate reserves in stubble. Interestingly, high temperature stimulated the accumulation of starch and ethanol-soluble carbohydrates in plants cut to 7.5 cm. The similar trends were also observed in protein, amino acids, nitrate, and ammonium. These responses were not pronounced in plants cut to 2.5 cm, presumably due to inhibited photosynthesis and photosystem II photochemistry. Overall, we anticipated that heat-activated metabolite accumulation is part of adaptive response to the stress. However, modified allocation of carbohydrate and nitrogen reserves leads to reduced vegetative regrowth upon defoliation. These data suggest that cutting height management for orchardgrass may be more effective for its regrowth vigor and productivity in cool seasons or when cool weather follows hay harvest.